Nanotechnology and medicine improvement - Filipe, J. A. (International Journal of Academic Research, 2015)
Nanotechnology has become an extraordinarily hopeful area in several human domains. Many scientific disciplines are developing their works in this area since the emergence of nanoscale, giving their contribution to the development of nanosciences. Many recent researches in areas as physical sciences, molecular engineering, biology, biotechnology and medicine for example are contributing for the investigation of biosystems at a nanoscale. Nanotechnology and nanobiosystems are becoming a privileged domain to reach an advanced level in the human development in many fields, as the examples of the biotechnology processes, the synthesis of new drugs and their delivery on a live body, the regenerative medicine and the new technologies in medicine (biotechnology and nanotechnology), body area networks for telemedicine (nanomedicine, nanoimaging, nanotechnological implants, in-body diagnostic systems, nanobiomedical wired devices, etc), or the application on the sustainability of the environment. Nanoscale may provide the tools to get improved conditions to investigate biosystems and to get advances with nanomaterials. These nanoscales, used in biosystems, contribute to enhance very innovative and promising results in medical area. Improvements in the telemedicine and on health are expectable with new systems operations and new nanotechniques. Many ethical problems and also legal and social implications are posed and the need for discussing this theme shows the importance of nanotechnology to the society and the consequences, both positive and negative, that the development of nanotechnology will have to mankind in the future.